Cooling Between Exercise Bouts and Post-exercise With the Fan Cooling Jacket on Thermal Strain in Hot-Humid Environments - Otani, Hidenori; Fukuda, Makoto; Tagawa, Takehiro (Frontiers in Physiology, 2021)
This study investigated the effects of cooling between exercise bouts and post-exercise with a commercially available fan cooling jacket on thermal and perceptual responses during and following exercise in hot-humid environments. Ten male athletes completed two 30-min cycling bouts at a constant workload (1.4 watts·kg−1 of body mass) with a 5-min recovery period in between. Exercise was followed by a 10-min recovery period. In an environmental chamber (33°C, 65% relative humidity), participants performed two trials with (FCJ) or without (CON) the fan cooling jacket on a T-shirt during the 5-min inter-exercise and 10-min post-exercise recovery periods. Mean, chest and upper arm skin temperatures, and thermal sensation and comfort were lower in FCJ than CON trial during and following exercise (P<0.05). Thigh and calf skin temperatures, infrared tympanic temperature and heart rate were lower in FCJ than CON trial during the experimental trials (P<0.05). The rates of fall in mean, chest and upper arm skin temperatures, infrared tympanic temperature and thermal sensation and comfort were faster in FCJ than CON trial during both recovery periods (P<0.05). There were faster rates of fall in thigh and calf skin temperatures and heart rate in FCJ than CON trial during the post-exercise recovery period (P<0.05). No difference was observed between trials in the rating of perceived exertion (P>0.05). This study indicates that cooling between exercise bouts and post-exercise with the fan cooling jacket would effectively mitigate thermal strain and perception/discomfort during and following exercise in hot-humid environments. This garment would reduce whole-body skin temperature quickly while promoting falls in lower-body as well as upper-body skin temperatures.